(untitled) (Journal of Dhaka Medical College, 2016)
Objective: This study was aimed to identify the distribution patterns of ABO and Rh-D blood group among the blood donor attending at transfusion medicine department DMCHin order to promote social awareness and safe blood transfusion among the population. Method: It was a cross sectional study conducted in the Department of Transfusion Medicine, Dhaka Medical College Hospital, Dhaka, from January to December 2014. After proper ethical consideration, a total of 39,512 blood donors were included in this study. They were selected irrespective of age and sex by systematic random sampling. ABO and Rh-D blood groups were determined by the antigen antibody agglutination test in our blood bank by standard tile techniques. Results: Among 39,512 blood donors male blood donors were 31,602(79.98%), female blood donors were 7,910(20.01%).14,817(37.5%) blood donor were identified as having blood group B, while 12,565 (31.8%) were blood group O, 8614( 21.80%) and3516( 8.9% )were blood group A and AB respectively. Rh-D positive were 38,247(96.79%) and Rh-D negative were 1,265(3.2%). J Dhaka Medical College, Vol. 24, No.1, April, 2015, Page 53-56